Education premiums and skilled migration: Lessons for an educational policy - Camelia Tigau; Bernardo Bolaños Guerra (Arizona State University, 2015)
This paper examines the relationship between skills prices (wage premiums) and inequality in migrant sending countries (mainly from Latin America) and explores the implications for education policies. Most of the evidence is based on the case of Mexico, a Latin American country that is also an Organisation for Economic Co‑operation and Development (OECD) member. Despite the belief that Latin American countries tend to pay less for their skilled workers than developed countries, they invest a considerable amount of their Gross Domestic Product (GDP) in education and sometimes in scholarships abroad. Therefore, our main question is: Are skill prices really so proportionately low in Latin America?  Likewise, what are the impacts of skills prices on migration in Latin America, and Mexico in particular? And, what is the importance of "brain drain" in terms of the relationship between migration and education? We find that despite the enormous inequality in the region, skills prices are not low. Furthermore, high expenditures on education combined with low skills prices do not necessarily result in brain drain. Other factors, such as perceptions of insecurity and corruption, have a stronger effect on the migration of Mexican professionals. Likewise, although high skills prices may lead to economic development, they may also increase social inequality, leading to greater brain drain. Therefore, the expansion of higher education is recommendable even if it reduces salaries and wage premiums in the short term.